va rooog dau coroana!!!!
Răspunsuri la întrebare
Răspuns de
1
(2^n+3 × 3^n+2^n ×3^n+1 + 6^n) : 6^n =
(2^n × 2^3 × 3^n + 2^n × 3^n × 3 + 6^n) : 6^n=
( 6^n × 8 + 6^n × 3 + 6^n) : 6^n =
6^n × ( 8 + 3 + 1) : 6^n =
6^n × 12 : 6^n =
12
__
(2^n × 2^3 × 3^n + 2^n × 3^n × 3 + 6^n) : 6^n=
( 6^n × 8 + 6^n × 3 + 6^n) : 6^n =
6^n × ( 8 + 3 + 1) : 6^n =
6^n × 12 : 6^n =
12
__
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Geografie,
8 ani în urmă
Limba română,
9 ani în urmă
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă